Retaining problems or solutions? The post‐acquisition performance implications of director retention - Campbell, Robert J.; Busenbark, John R.; Graffin, Scott D.; Boivie, Steven (Strategic Management Journal, 2021)
Abstract Research Summary Director retention is a common practice during acquisitions, whereby the acquiring firm adds at least one director from the target onto its board. Despite the regularity of the phenomenon, little is understood about the post‐acquisition financial implications of director retention. In this exploratory study, we investigate the financial impact (via long‐term investor value appropriation) of director retention in a sample of acquisitions among publicly traded firms. Our empirical analyses consistently illustrate negative financial ramifications of director retention for the acquiring firm across multiple analytic models, time horizons of performance, and samples. We delineate implications for research on boards of directors and acquisitions, and we offer preliminary theoretical logic and empirical analyses for future scholarship to elucidate the mechanisms driving antecedents and outcomes of director retention. Managerial Summary Despite the prevalence of director retention—a practice where an acquirer adds at least one director from the target onto the board of the ongoing firm—research on the topic is equivocal about the financial implications of this practice. We argue this is a crucial oversight because new directors can have an incredible influence on the trajectory of the firm and its subsequent performance, a fact that is particularly true in the turbulent post‐acquisition period. In our study, we empirically examine the impact of director retention on post‐acquisition performance. Across multiple analyses and time intervals of performance, we consistently find that director retention is negatively associated with the performance of the acquiring firm. Accordingly, our findings suggest that acquirers should generally approach direction retention with caution.